SINERGITAS DESA DINAS DAN DESA ADAT DALAM MENERTIBKAN PENDUDUK NONPERMANEN: (Studi Pada Desa Dinas dan Desa Adat Dalung) - Komang Reisha Oktavian Wiraparamita Giri; Dadan Kurniansyah; Sopyan Resmana Adiarsa (LPPM Universitas Abdurrab, 2026)
This study explores the synergy between the Village Office and the Dalung Traditional Village in regulating non-permanent residents through communication and coordination. This qualitative research with a phenomenological approach aims to determine, analyze and describe the communication and coordination carried out by the Village Office and the DalungTraditional Village in regulating non-permanent residents through the experiences of the actors involved. The analysis of this study uses the synergy theory of Najiyati and Rahmat which includes communication, namely communicators, media, openness and trust as well as feedback and coordination which includes continuity, dynamics, clear objectives and formulation of authority and responsibility. The results of the study indicate that two-way communication has been established between the Village Office and the Dalung Traditional Village in implementing the non-permanent population inspection activities through compatible communicators with media that are easily accessible to the actors who realize openness to each other so as to foster trust and create positive feedback. The synergy between the Village Office and the Dalung Traditional Village is also evident in the coordination established by the actors, spanning the planning and evaluation stages. This is flexible and dynamic, with clear and aligned objectives and clear delegation of tasks for each actor. The synergy between the Village Service and the Dalung Traditional Village is reflected in the existence of communication and coordination that complement each other and the synergy between the two village institutions also provides benefits for the village government and the regional government in controlling the rate of non-permanent population in the area.